A Clinico-Hematological Study of Cases of Leucoerythroblastic Reaction - Waghmare, Tejaswini; Prabhat, Daksha; D, Naveen Vairamoorthy (Annals of Pathology and Laboratory Medicine, 2019)
Background: Leucoerythroblastic Reaction (LER) is defined as the presence of immature red cells and immature white cells of the myeloid series in peripheral blood. Literature has revealed various causes for LER, which include hemolyticanemia, infections, megaloblastic anemia, liver diseases and others. Objectives: To study the hematological changes, especially peripheral blood smear (PBS) findings in LER cases. Methods: A total number of 100 consecutive cases which revealed LER on peripheral blood smear (PBS) were included in this study. Various hematological parameters such as. hemoglobin, total leucocyte count, platelet count as obtained from the automated blood cell counter and PBS findings were analysed. Results: In the present study, majority of the cases (30%) were in the age range of 21 to 30 years, with equal gender distribution. Anemia was seen in 87% of the cases, leucocytosis in 79% and thrombocytopenia in 60%. Polychromasia with increased reticulocytes was noted in 55% of the cases. Nucleated RBCs were noted in all cases. All cases showed shift to left in the myeloid series. Commonest cause of LER encountered was hemolytic disease (29%) followed by liver diseases (22%) and septicemia (18%). Conclusion: The present study emphasizes various etiologies of LER and the importance of reporting LER in PBS. Examination of peripheral blood smear for morphology of RBCs, WBCs and platelets gives a clue to the etiology.